Гражданственность и ценностные приоритеты студенческой молодежи в условиях регионального полиментального образовательного пространства - Zakharova A. N., Dulina G. S. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
The article provides the current state of analysis of scientific research on the issue of citizenship. Empirical studies the level of citizenship and patriotism, value priorities of students in the conditions of regional polymental educational space is devoted the article.
Keywords: патриотизм; гражданственность; students; базовые ценности; patriotism; ценностные приоритеты; региональное полиментальное образовательное пространство; value priorities; студенческая молодежь; citizenship; basic values; regional polymental educational space